The Sage handbook of aging, work and society - Field, John 1949-; Burke, Ronald J.; Cooper, Cary L. (Los Angeles SAGE, 2013)
Key international contributors come together to create a definitive map of the subject. Framed by an authoritative introductory chapter, 'The SAGE Handbook of Aging, Work and Society' offers a critical overview of the most significant themes and topics, with discussions of current research, theoretical controversies and emerging issues
The Aging Workforce: Individual, Organizational and Societal Opportunities and Challenges / Ronald J. Burke, Cary Cooper and John Field -- World Population in HIstorical Perspective / Tommy Bengtsson and Kirk Scott -- Research on Age Diversity in the Workforce: Current Trends and Future Research Directions / Florian Kunze andStephen A. Boehm -- Prolonging Working Life in an Aging World: A Cross-national Perspective on Labor Market and Welfare Policies Toward Active Aging / Anne-Marie Guillemard -- Migration and Workforce Aging / John Field-- Work Performance and the Older Worker / Margaret E Beire and Ruthe Kanfer -- Age and Work Motives / Cort W.Rudolph, Boris B. Baltes and Keith L. Zabel -- New Patterns of Late-Career Employment / Kerr Inkson, Margaret Richardson and Carla Houkamau -- Care Work and New Technologies of Care for Older People Living at Home / Celia Roberts, Maggie Mort and Christine Milligan -- Aging, Work and the Demographic Dividend in South Asia / Penny Vera-Sanso -- Age and Generational Differences inWork Psychology: Facts, Fictions, and Meaningful Work / Paul Fairlie -- Comparative Age Management: Theoretical Perspectives and Practical Implementations / Stephan A. Boehm, Heike S. Schröder and Florian Kunze -- DemographicChallenges for Human Resource Management: Implications from Management and Psychological Theories / Birgit Verworn, Christiane Hipp and Doreen Weber -- Age Stereotypes in the Workplace: Multidimensionality, Cross-cultural Applications, and Directions for Future Research / Richard A. Posthuma and Laura Guerrero -- Older Workers, Occupational Stress and Safety / Gary A. Adams, Sarah DeArmond, Steve M. Jex and Jennica R. Webster -- Training Older Workers: A Review / Yu-Shan Hsu -- Older Workers in the Professions: Learning Challenges and Strategies / Tare Fenwick -- Quality of Work, Wellbeing and Retirement / Johannes Siegrist and Morten Wahrendorf -- Working Caregivers in the 'Sandwiched Generation' / Margaret B. Neal, Leslie B. Hammer, Ayala Malach Pines, Todd E. Bodner and Melissa L. Cannon -- TheSocial Connections of Older Europeans / Martil Kohli and Harald Künemund -- Engaging Elders in Community and Society / Stina Johansson -- Learning in Later Life / Franz Kolland and Anna Wanka -- The Role of Social Networking Games in Maintaining Intergenerational Communications for Older Adults / Yunan Chen, Jing Wen and Bo Xie -- Making a Case for the Existence of Generational Stereotypes: A Literature Review and Exploratory Study / Elissa L. Perry, Apivat Hanvongse andDanut A. Casoinic -- Reconstructing Work and Retirement: Labour Market Trends and Policy Issues / Chris Phillipson-- Policies for Older Adult Learning: The Case of the European Union / Marvin Formosa -- Optimizing the Long Future of Aging: Beyond Involvement to Engagement / Jacquelyn Boone James, Marcie Pitt-Catsouphes, Jennifer Kane Coplon and Betty Eckhaus Cohen -- The Measurement ofMultiple Dimensions of Subjective Well-being in Later Life/ Bram Vanhoutte -- Legal Aspects of Age Discrimination / Malcolm Sargeant
Includes bibliographical references and index.
Keywords: Age and employment; Older people -- Employment; Age discrimination in employment; Older people -- Social conditions; Aging -- Social aspects